2011
DOI: 10.3354/dao02391
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial skin flora variation and in vitro inhibitory activity against Saprolegnia parasitica in brown and rainbow trout

Abstract: Variations in the number and diversity of bacteria from the skin of brown trout Salmo trutta L. and rainbow trout Oncorhynchus mykiss Walbaum were surveyed from different rivers and fish farms in northern Spain. In addition to determining bacterial populations in skin samples of healthy fish, bacterial populations were determined from skin lesions (of brown trout only) infected with Saprolegnia parasitica, the causal agent of saprolegniosis. Mean bacterial counts from skin lesions of brown trout suffering from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 22 publications
1
31
0
1
Order By: Relevance
“…In this context purified plant‐derived compounds comprising cynatratoside‐C (Fu, Zhang, Xu, Liang, et al., ), sanguinarine (Yao et al., ), dihydrosanguinarine and dihydrochelerythrine (Yao et al., ) and pentagalloylglucose (Zhang, Xu, & Klesius, ) have exhibited antiparasitic effects in the laboratory but despite the promising report questions on residual and toxic effects in fish and consumers remain unsolved. Other control methods involving easily biodegradable molecules are therefore being investigated and among these surfactants produced by naturally occurring bacteria such as Pseudomonas and Aeromonas have attracted interest (Carbajal‐Gonzalez, Fregeneda‐Grandes, Suarez‐Ramos, Rodriguez‐Cadenas, & Aller‐Gancedo, ; Lategan & Gibson, ). Biosurfactant H6 produced by Pseudomonas was recently reported to suppress another fish pathogen, the oomycete Saprolegnia diclina (de Bruijn et al., ; Liu et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…In this context purified plant‐derived compounds comprising cynatratoside‐C (Fu, Zhang, Xu, Liang, et al., ), sanguinarine (Yao et al., ), dihydrosanguinarine and dihydrochelerythrine (Yao et al., ) and pentagalloylglucose (Zhang, Xu, & Klesius, ) have exhibited antiparasitic effects in the laboratory but despite the promising report questions on residual and toxic effects in fish and consumers remain unsolved. Other control methods involving easily biodegradable molecules are therefore being investigated and among these surfactants produced by naturally occurring bacteria such as Pseudomonas and Aeromonas have attracted interest (Carbajal‐Gonzalez, Fregeneda‐Grandes, Suarez‐Ramos, Rodriguez‐Cadenas, & Aller‐Gancedo, ; Lategan & Gibson, ). Biosurfactant H6 produced by Pseudomonas was recently reported to suppress another fish pathogen, the oomycete Saprolegnia diclina (de Bruijn et al., ; Liu et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…We used 15 bacterial isolates obtained from the skin of brown trout ( Salmo trutta L.) and rainbow trout ( Oncorhynchus mykiss Walbaum) that inhibit S. parasitica in vitro (Carbajal‐González et al, ; ) (Table ). All 15 bacteria were used to test saprolegniosis biocontrol through addition to water, and two of them, LE89 and LE141, through addition to feed.…”
Section: Methodsmentioning
confidence: 99%
“…Several in vitro studies have demonstrated that some bacteria inhibit Saprolegnia spp., including Pseudomonas fluorescens (Bly, Quiniou, Lawson, & Clem, ; Carbajal‐González, Fregeneda‐Grandes, González‐Palacios, & Aller‐Gancedo, ; Carbajal‐González, Fregeneda‐Grandes, Suárez‐Ramos, Rodríguez‐Cadenas, & Aller‐Gancedo, ; Hatai & Willoughby, ; Liu et al, ), Alteromonas sp. , Pseudomonas alcaligenes, Pseudomonas saccharophila, Aeromonas caviae and Aeromonas eucrenophila (Hussein & Hatai, ), Serratia marcescens (Zhang, Yang, Li, & Gao, ), Bacillus subtilis (Liu, Lu, Liu, & Zhou, ), Aeromonas media (Lategan & Gibson, ), Aeromonas sobria, Pantoea agglomerans, Serratia fonticola, Xhantomonas reflexus and Yersinia kristensenii (Carbajal‐González et al, ), Lactobacillus plantarum (Nurhajati, Atira, & Kadek Indah, ) and Pseudomonas aeruginosa (Moghaddam, Hajimoradloo, Ghiasi, & Ghorbani, ). However, their action in vivo has only been studied in eel Anguilla australis (Lategan et al ), silver perch Bidyanus bidyanus (Lategan et al ) and eggs of rainbow trout Oncorhynchus mykiss during incubation (Heikkinen et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…have been described in several studies (Hatai & Willoughby 1988, Bly et al 1997, Hussein & Hatai 2001, Lategan & Gibson 2003, Zhang et al 2008, Nurhajati et al 2012, Ran et al 2012. Carbajal-González et al (2011) found that certain bacteria from the skin of brown trout Salmo trutta and rainbow trout Oncorhynchus mykiss can inhibit or render difficult the in vitro growth of Saprolegnia parasitica. Hence some of these bacteria might be useful in the biological control of saprolegniosis.…”
Section: Introductionmentioning
confidence: 97%